Short-term metabolic effects of breaking up sedentary behaviors - De Jong, Nathan Paul, author; Hickey, Matthew S., advisor; Bergouignan, Audrey, committee member; Braun, Barry, committee member; Melby, Christopher L., committee member (Colorado State University. Libraries, 2022)
"Sit Less, Move More" has become a widespread public health message due in part to the recognition that sedentary behaviors (i.e., sitting) are associated with all-cause mortality and increased risk for obesity, diabetes, cardiovascular diseases and some cancers, even when accounting for time spent in moderate-to-vigorous physical activity. Recent epidemiological and experimental evidence from acute and short-term studies indicate that reducing and breaking up sedentary behaviors (i.e., sitting) may be a useful strategy for glucose control. Acute experimental trials (5-12 hr exposure) demonstrate that breaking up sedentary time with short-frequent bouts of physical activity is associated with lower postprandial glucose and insulin concentrations while a time-matched single-continuous bout is associated with lower postprandial triglyceride concentrations in response to standardized meals. This suggests differential substrate oxidation may be responsible for the changes in postprandial metabolites. However, what is unknown is (1) whether breaking up sedentary behaviors with short-frequent bouts of physical activity is a strategy that can be implemented in the daily life of sedentary, physically inactive adults; (2) whether the acute metabolic benefits previously observed are sustained or diluted beyond the acute exposure period (> 5-12 hr); (3) whether the effects are due to the active breaks per se or to increases in total energy expenditure and/or total active time and (2) the characterization of potential underlying physiological, cellular, and molecular mechanisms. The primary objective of this dissertation is to investigate the feasibility of implementing short-frequent bouts of physical activity to break up sedentary behaviors into daily life over the short-term (4-day) in those who are habitually inactive and the effect on nutrient metabolism when energy expenditure and balance are matched. We hypothesized that breaking up sedentary behaviors with short-frequent bouts of physical activity is a feasible lifestyle intervention to increase physical activity which will be associated with attenuated glycemia by an increase in postprandial carbohydrate oxidation. In a randomized cross-over study, we compared the short-term effects (4-day) of breaking up sedentary behaviors with short-frequent bouts of moderate intensity physical activity (MICRO: 5-min walk bout every hour for 9 consecutive hours per day) to a time-matched single-continuous bout of moderate intensity physical activity (ONE: 45-min continuous walking bout per day), and a sedentary control (SED: habitual sedentary behaviors and physical inactivity each day) in inactive male and female adults with overweight or obesity. To reach our overall objective, three independent specific aims were pursued: 1) to determine the feasibility of implementing MICRO compared to ONE on daily time spent sitting and physically active over the short-term; 2) to determine the effect of MICRO compared to ONE on nutrient metabolism and insulin sensitivity; 3) to characterize the short-term effect of MICRO compared to ONE on permeabilized skeletal muscle fiber respiration and gene expression of proteins involved in the regulation of metabolic pathways. Results from this dissertation demonstrate that 1) MICRO is a feasible intervention to promote physical activity both on workdays and non-working days in those who are at high risk for metabolic disease; (2) At the same energy expenditure and balance, MICRO resulted in a greater reliance on carbohydrate as fuel during the waking period when the bouts were performed and over 24 hr. In contrast, a single isoenergetic continuous bout of moderate intensity walking increased 24 hr total and dietary fat oxidation. Both physical activity interventions lowered postprandial insulin and improved fasting indexes of insulin sensitivity compared to SED; 3) While no changes were observed after MICRO in mitochondrial oxidative capacity, MICRO is a sufficient stimulus to promote adaptations in skeletal muscle augmenting pathways associated with substrate oxidation. Independent of detectable differences in insulin sensitivity, total active time, and energy expenditure, breaking up sedentary behaviors with short-frequent bouts of physical activity spread throughout the day is a viable lifestyle intervention for glucose control compared to the same amount of physical performed as a single continuous bout with the rest of the day spent sedentary. This evidence can be used to refine future physical activity guidelines to prevent and treat metabolic diseases, not in terms of intensity of exercise per day per week but in terms of avoidance of sedentary activities through short bouts of physical activity.